The Social Space of Language : Vernacular Culture in British Colonial Punjab - Mir, Farina (Book collections on Project MUSE., 2010)
This rich cultural history set in Punjab examines a little-studied body of popular literature to illustrate both the durability of a vernacular literary tradition and the limits of colonial dominance in British India. Farina Mir asks how qisse, a vibrant genre of epics and romances, flourished in colonial Punjab despite British efforts to marginalize the Punjabi language. She explores topics including Punjabi linguistic practices, print and performance, and the symbolic content of qisse. She finds that although the British denied Punjabi language and literature almost all forms of state patron.